Solidaritas Sosial dalam Komunitas Kurir Singgang di Barito Utara - Kurniawan, Hendra; Hakim, Arif Rahman (Prodi Sosiologi FISIP ULM, 2025)
The Kurir Singgang Community, also known as Babuhan Kurir, in North Barito, is a social group formed based on shared profession as couriers and a mutual interest in the world of automotive culture. Along with the passage of time and the dynamics of its members’ lives, the community has undergone significant changes in both membership composition and the forms of solidarity established. This study aims to explore how social solidarity within the Kurir Singgang community is formed, maintained, and developed, shifting from profession-based solidarity to solidarity rooted in shared interests and collective values across diverse backgrounds. A qualitative case study approach was employed, with data collected through direct observation, in-depth interviews, and documentation of community activities. The findings reveal a transformation from an exclusive to an inclusive character as an adaptation to the challenges of courier work and changing member identities. Social solidarity, which initially stemmed from professional commonality, has been strengthened through cooperation, mutual assistance, and emotional attachment in the community’s daily life. This process aligns with Emile Durkheim’s theory of social solidarity, illustrating the transition from mechanical to organic solidarity. While the community has managed to endure and evolve, challenges remain, including differences in commitment levels and disparities in member participation. This research contributes to the broader study of community dynamics and social change in the context of informal labor societies. Future studies are recommended to focus on aspects of community leadership, mechanisms of collective decision-making, and the role of social media in shaping and sustaining social solidarity in the digital era.